Analysis of dynamic and fatigue effects in a old metallic riveted bridge - Fernando Marques (2014)
The fatigue behaviour of steel railway bridges is a complex phenomenon. On the one side, the Engineer must face the problem of dynamic amplification of the loads and their randomness, on the other side, the fatigue resistance is highly dependent on the load itself, since for different stress levels the material can sustain different number of cycles. This complexity makes the identification of the critical elements for structural safety a difficult task. In this context, and in the framework of the European research project FADLESS, the Laboratory of Vibrations and Monitoring (ViBest) of FEUP has conducted extensive research concerning the evaluation of dynamic effects and fatigue analysis of an old riveted railway bridge. Owing to the importance of this phenomenon, complementary numerical and experimental approaches have been used to assess fatigue effects. This article describes the main steps taken towards the goal of evaluating the dynamic behaviour and the fatigue life of this structure.